Persepsi Pengunjung Pameran HCPSN terhadap Konservasi Alam dan Strategi Promosi Konservasi di Masa Pandemi - Sugiarti Rachim; Hendra Gunawan (Sekolah Vokasi, Universitas Gadjah Mada, 2022)
National Flower and Animal Love Day (HCPSN), celebrated every 5 November, aims to increase awareness, protection, conservation, and sustainable use of national flowers and animals. One way to commemorate HCPSN is to organize an exhibition on biodiversity conservation. The 2020’s HCPSN exhibition held at Bogor Botanical Gardens. the research team surveyed by distributing questionnaires to 90 visitors to obtain data on their perceptions and attitudes towards nature conservation and opinions on environmental education. The survey found that only some respondents knew about HCPSN (53.3%), National Nature Conservation Day (41.1%), Environment Day (52.2%), and International Forest Day (36.7%). Respondents realized that nature conservation is the responsibility of all citizens (67.8%) and 21.2% of respondents support and participate in environmental conservation actions. As many as 61.1% of respondents think that environmental education in schools is still lacking, therefore they consider it necessary to have environmental education in schools, both in the form of separate subjects (57.0%), integrated into other materials (28.0%) and extracurricular (15.0%). The survey also found that environmental education was obtained by respondents from schools (21.5%), books (16.2%), social media (13.1%), museums (13.1%), television (12.6%), parents (7.9%), exhibitions (6.3%), newspapers and magazines (4.7%), and brochures or posters (4.7%). The respondent's educational background has a significant effect on the perception of endangered flower, and the first source of knowledge about nature conservation obtained by the respondent is highly significant correlation with the respondent's perception of the endangered flower, but not for national animals. Based on these findings, a strategy for promoting nature conservation can be drawn up, especially during a pandemic.